The development of the economic sciences: two contemporary tendencies - Jajuga, Krzysztof (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2021)
The paper discusses two important trends that have shaped research in the economic sciences over the last two decades. The first one is the growing interdisciplinarity of economic research. The second one is the impact of technological changes on research in the economic sciences. The paper presents the author’s systematization of these problems.